Pengaruh Metode Hafalan Mufrodat Dalam Peningkatan Keterampilan Membaca Bacaan Bahasa Arab - Khairunnisa, Nurul; Sewang, Anwar; Zulkiflih, Zulkiflih; Nurhidayah, Nurhidayah; Munawarah, Munawarah (Al-Wazan: Journal of Arabic Education, 2024)
Learning Arabic is not as easy as learning our first language, namely Indonesian or Bugis, Mandar, Makassar. Teaching foreign languages, especially Arabic, is different from other languages, because teaching Arabic prioritizes several skills, namely listening skills, reading skills, speaking skills and writing skills. This study aims to determine the influence of memorization methods in improving Arabic reading comprehension in grade X students of Madrasah Aliyah Negeri 2 (MAN 2) Polewali Mandar, Matakali District, Polewali Mandar Regency. This study involved two variables, namely the independent variable is the influence of the mufrodat memorization method while the bound variavel is the ability to read Arabic readings of learners. This type of research uses a type of quantitative descriptive research. The subjects of this study were students of grade X Madrasah Aliyah Negeri 2 (MAN 2) Polewali Mandar, with sampling techniques. Furthermore, the research instruments used were test sheets and questionnaires to determine the effect of the Mufradat memorization method in improving Arabic reading comprehension in grade X students of Madrasah Aliyah Negeri 2 (MAN 2) Polewali Mandar. The data obtained were analyzed using descriptive statistical analysis. The results proved that mastery in memorizing mufradat has a strong influence on Arabic reading skills as evidenced by a significant correlation between variable X (mastery of memorizing mufradat) and variable Y (skill in reading Arabic reading). This is proven by obtaining a value of 0.005 (0.000 < 0.005) the relationship is linear, which means that the higher the level of mastery of memorizing mufradat, the higher the ability to read Arabic readings in students